295 SPEP IT UP! DEVELOPING AN ALGORITHM FOR ABNORMAL SERUM PLASMA ELECTROPHORESIS RESULTS IN HIP FRACTURE PATIENTS. (25th October 2022) - Davey, N; Fitzgerald, R; Fauzi, MYBM; Khan, MA; O'Donnell, N; Kumar, S; Bambrick, P; Pope, G; Mulcahy, R; Cooke, J; O'Regan, N
Abstract: Background: Hip fracture is a common manifestation of osteoporosis. All patients who sustain a hip fracture should receive a specialist bone health assessment, including Serum Protein Electrophoresis (SPEP) because plasma cell disorders such as multiple myeloma are an important differential diagnosis. SPEP results can be challenging to interpret without training and expertise. We aimed to review the proportion of abnormal SPEP results in hip fracture patients and used a newly developed algorithm to assess urgency of referral to haematology. Methods: The Orthogeriatrics and Haematology teams collaborated to develop an algorithm to help facilitate decision making in hip fracture patients with abnormal SPEP results. A retrospective study was then conducted using data from the local Hip Fracture Database from Quarters 1 and 3 in 2020, and the hospital electronic laboratory system. The algorithm was used to retrospectively determine which patients warranted haematology review. The electronic appointment system was then accessed to review whether those who warranted haematology referral had appointments on the system. Results: Of 270 hip fracture presentations, 19 duplicate records were excluded. Five patients had no data and three patients had passed away. Of the remaining 243 patients, 193 (79.42%) had SPEP's sent. Abnormalities were detected in 116 patients (47.74%). According to the SPEP referral pathway, two patients warranted routine referral and one patient required an urgent referral, none of whom appeared to have been referred to haematology. Two patients who did not warrant haematology referral were already under haematology for different conditions. Conclusion: Not all patients who sustain acute osteoporotic fractures with an abnormal SPEP result require haematology referral. The need for an urgent or routine haematology can be guided by the SPEP result along with other clinical features. With the introduction of this pathway, it is proposed that all hip fracture patients will be triaged in a timely, appropriate, and consistent manner.